1983
DOI: 10.1137/0720004
|View full text |Cite
|
Sign up to set email alerts
|

Fast Numerical Solution of the Biharmonic Dirichlet Problem on Rectangles

Abstract: A new method for the numerical solution of the first biharmonic Dirichlet problem in a rectangular domain is presented. For an N x N mesh the complexity of this algorithm is on the order of N arithmetic operations. Only one array of order N and a workspace of size less than 10N are required.These results are therefore optimal and the algorithm is an order of magnitude more efficient than previously known methods with the possible exception of multi-grid. The method has an iterative part where a problem with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…We refer to [38] as well as [15,16,19,44,45] for this case, which is important in plate theory but is excluded from the present analysis.…”
Section: Weak Formulation and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to [38] as well as [15,16,19,44,45] for this case, which is important in plate theory but is excluded from the present analysis.…”
Section: Weak Formulation and Boundary Conditionsmentioning
confidence: 99%
“…In this paper we develop preconditioners for spatially discretized versions of this system, for instance via finite element methods, thereby relying on the existence of efficient methods and software for each component of the system [18,20,21,23,37,40,48,49,50,52,53,54], especially on graded meshes [1,26,49,51]. Similar ideas have been developed for the bi-harmonic operator with Dirichlet boundary conditions u = ∂ ν u = 0, typical in structural mechanics, and quasi-uniform meshes in [15,16,19,44,45]. Materials science and fluid dynamics problems come with different boundary conditions which yield the operator splitting (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…The preconditioning by the block diagonal part diag (L n , L 22 ) is investigated. Each block L u corresponds to the biharmonic problem with Au rather than u n specified on two opposite sides of the square ft. Bjjdrstad [2] has observed that this problem is easy to solve, since séparation of the variables is possible. Assuming that Au is specified at the left and right part of the boundary, we choose a row-wise ordering of the …”
Section: Further Preconditioning the Biharmonic Equation In A Squarementioning
confidence: 99%
“…The second member of the right hand side of (7.11) can be estimated using LEMMA 7.4 ; Let v (2) = (t? 0 , 0 Inserting (7.14) into (7.13) complètes the proof.…”
Section: Discrete Norms and Matrix-representationsmentioning
confidence: 99%
See 1 more Smart Citation